Proposed upgrading of Taha Cafeteria for Tabung Haji at Basement, Tabung Haji Headquarters Building, 201, Jalan Tun Razak, 50400 Kuala Lumpur / Nur Sufira Roszlan - Roszlan, Nur Sufira (2010)
A final year student pursuing a diploma course in Interior Design is required to prepare a final year project. The design of the project should be related closely to current issues or similar to it. The knowledge and skill acquired during the duration of the course should be put to practise onto the drawing board. This also includes the research, case study, interviewing of clients, designing proposals, preparing artwork, preparing presentation drawings, design development and last but not least the final presentation. The proposed product for this project is cafeteria. The site placed at Basement, Tabung Haji Headquarters Building, 201, Jalan Tun Razak, 504000 Kuala Lumpur. The proposed site, TAHA Cafeteria was designed for Tabung Haji but the operator of the cafeteria is TH Global Services Sdn. Bhd.one of Tabung Haji shareholders. Tabung Haji is Malaysian Hajj pilgrims fund board. Tabung Haji facilities saving for the pilgrimage to Makkah through investment in Shariah-compliant vehicles. Three mains of the client activities are funds, invests and hajj. Tabung Haji Headquarters Building itself is one of the city's famous buildings. The building is a single building with 151.83 meters architectural height and 38 floors above the ground. The construction type of the building is skyscraper and the building structural material is concrete. The architects who design the building site are Hijjaz Kasturi Association and the architectural style is modernism. The building main usage is commercial office and the site usage is parking. Three case study of the cafeteria that had been observed are Subway at The Curve, The Tarik Place at Damansara Mutiara and The Craven Cafe at Wangsa Maju, Kuala Lumpur.The space requirement in TAHA Cafeteria includes many spaces that needed extra research on space planning as it deals with traffic flow for customers and staffs and other proposed area inside such as dining area, food display area, bar counter area, hand wash basin area, cashier counter area, kitchen, VIP area, LCD broadcast area and washroom. In this design proposal for designing the interior of TAHA Cafeteria, there are some important things to be included so that the final product would reach the goal and fulfill the client's needs. Those important things are the criteria, the objectives and also the design goal. As a conclusion, all of the method that is being studied is the continuation from the writer's knowledge about this project. The proposed design is based on the problem-solving method on those design principles.